Student Anxiety About Online Learning During The Covid-19 Pandemic - Nurul Anwar; Mohd Sani Ismail; Sar'in Sar'in (Institute of Computer Science (IOCS), 2022)
The use of online platforms is on the rise. Coupled with the COVID-19 pandemic has changed many aspects of modern life, especially education. The existence of online learning also has psychological. Anxiety is a typical response that expresses